Cell Stress Proteins - Calderwood, Stuart K. (Protein Reviews, 2007)
This comprehensive volume, written by experts in the field, provides a current understanding of the molecular properties of the heat shock proteins and their roles in health and disease. Cell Stress Proteins includes advances in several aspects of stress protein research, with chapters ranging from basic studies of the role of heat shock proteins in protein folding to reviews examining the breakdown of stress protein regulation during disease. It also provides analysis of the biochemical and molecular properties of heat shock proteins which can be utilized in evaluating their role in human physiology and pathology. Cell Stress Proteins is an ideal book for researchers, clinicians, physicians, and graduate students in the fields of biochemistry, cell biology, microbiology, immunology, and genetics.